Some aspects of socio-cultural integration of young repatriants - Zhailybayev, D.Zh.; Serikkaliyeva А.Е.; Taldybayeva, D.A. (Journal of Oriental Studies, 2020)
In particular, the cultural potential and the social status of the younger generation of Kandastar in historical homeland requires a revision of a number of issues. For instance, the activities of young people in construction, services, medicine and education allowed them to quickly adapt to the local society. In particular, the mutual integration of young people is significantly influenced by their education abroad and traditionalism of mentality. One of them is the preservation of family relations, observance of traditional social relations and etiquette. This suggests that the connection between the older generation and the younger generation of repatriates in Kazakhstan is still preserved. Moreover, the position of young people in society has provided them with many opportunities for social and cultural adaptation. Key words: Kandastar, adaptation, integration, Kazakhstan, society, repatriate, education, construction, language.